Readiness or Trust That Make People Committed to Organizational Change? - Wustari L. Mangundjaya; Bonar Hutapea; Syifa Fauzia (Jurnal Scientia, 2023)
This research aimed to examine the impact of individual readiness for change and organizational trust on the affective commitment to change. The respondents of the research were 328 employees who work in various banking organizations who have facing changes in the Jabodetabek area Indonesia. Data were collected using Commitment to Change Inventory, Organizational Trust, and Readiness for Change scale, and were analyzed using regression analysis. Findings indicated that there was a positive and significant impact of individual readiness for change and organizational trust on affective commitment to change. It implies that people with high individual readiness for change and organizational trust also have a high affective commitment to change. This research also found that individual readiness for change had a stronger impact on the affective commitment to change than organizational trust, which can be concluded that developing people ready toward change is important.